Hakikat Peserta Didik Dalam Pendidikan Islam - Dessy Fadilla; Diana Agustina; Faradiza Ariska Br. Sitorus; Mardinal Tarigan; Marzuki Marzuki (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
In principle, education is described as a conscious effort to do what adults do at every stage of development to change a child's development. It can be seen that education has been going on since children set foot in this world and began to receive the educational process carried out by their parents. However, due to parental restrictions, the child then receives formal education at school in an organized formal institution. Education can be understood as an adult endeavor and is different for children at each stage of their development. Teachers and students are the main organs of education. Islam has its own views on education, especially children. This can be seen from the concept of instinct. Instinct is a basic element possessed by humans. This means that humans are good creatures that can be created according to instructions. Keywords: students, Islamic education